The Strategy for Developing Educational Pedagogical Competencies in Madrasah Tsanawiyah - Abdul Rahman (Jurnal Pendidikan dan Pengajaran, 2023)
It is crucial that educational establishments uphold the standard of teachers' pedagogical ability. There are a number of strategies that may be used to improve educators' competency, including performing their tasks as educators in a professional manner and trying to discipline oneself to engage in various activities that can foster competency growth. This research aimed to analyze the pedagogical competency development strategy for educators. The study used primary data through interviews and questionnaires of 63 informants as samples based on sample criteria of 3 principals, 30 educators and 30 students as informants. The findings show that the headmaster of the Madrasah Tsanawiyah, as a leader in each institution, employs a variety of strategies for enhancing pedagogical proficiency of educators by inspiring and involving educators to participate in a variety of scientific activities like energizing Subject Teachers Conference, Teacher Working Group, seminars, training, and workshops. It can be concluded that the growth of educators' pedagogical competency complies with national educational requirements. Moreover, it is crucial for educational institutions at all levels to create ways to uphold the standard of educator competencies.